1983
DOI: 10.1055/s-2007-969820
|View full text |Cite
|
Sign up to set email alerts
|

The Role of 9- and/or 10-oxygenated Derivatives of Geraniol, Geranial, Nerol, and Neral in the Biosynthesis of Loganin and Ajmalicine

Abstract: A number of deuterium labelled 9- and/or 10-oxygenated derivatives of geraniol, geranial, nerol, and neral were used as substrates in feeding experiments with a cell suspension culture of CATHARANTHUS ROSEUS. The 9- and 10-oxo derivatives of geraniol, geranial, nerol, and neral as well as 9,10-dihydroxygeraniol, 9-oxo-10-hydroxygeraniol, and 9,9,10,10-tetraethoxygeranial were found to be good precursors of the indole alkaloid ajmalicine. The compounds 9-hydroxygeraniol, 9-hydroxynerol, 9,10-dihydroxynerol, 9-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…and further hydroxylated and methylated to produce loganin (Yamamoto et al, 2002). Balsevich et al performed tracer experiments using compounds labeled with deuterium isotopes, demonstrating the role of 9-and/or 10-oxygenated derivatives of geraniol, geranial, nerol, and neral in the biosynthesis of loganin, and inferring a possible biosynthetic pathway between geraniol and loganin (Balsevich & Kurz, 1983). The order of hydroxylation at C-9 and C-10 was involved in the synthesis pathway, and the order of oxidation at C-1, C-9 and C-10 was also explored.…”
Section: Plant Resourcesmentioning
confidence: 99%
“…and further hydroxylated and methylated to produce loganin (Yamamoto et al, 2002). Balsevich et al performed tracer experiments using compounds labeled with deuterium isotopes, demonstrating the role of 9-and/or 10-oxygenated derivatives of geraniol, geranial, nerol, and neral in the biosynthesis of loganin, and inferring a possible biosynthetic pathway between geraniol and loganin (Balsevich & Kurz, 1983). The order of hydroxylation at C-9 and C-10 was involved in the synthesis pathway, and the order of oxidation at C-1, C-9 and C-10 was also explored.…”
Section: Plant Resourcesmentioning
confidence: 99%
“…89 A study of the biosynthesis of geraniol in PeZargonium graveolens has shown that the concentration of geranyl diphosphate (30) reaches a maximum in July if the plants grow in the Northern hemisphere, and that there is a correlation with the levels of isopentenyl diphosphate and of mevalonate kina~e.~O Cell-free extracts of Tanacetum vulgare convert geraniol (1 7) into epoxidized and hydroxylated products; this effect is most pronounced in whole plants during severe winters.91 The roles of 9-and 10-oxygenated derivatives of geraniol (1 7), nerol(l8), and the isomeric citrals (19) in the biosynthesis of loganin and ajmalicine have been discussed. 92 Suga and co-workers have put forwardg3 additional evidence that linalyl diphosphate (3 1) is the most immediate precursor of the cyclized products limonene ( 16) and a-terpineol (32). However, Banthorpeg4 has studied the metabolism of linalyl diphosphate (3 l), geranyl diphosphate (30), and neryl diphosphate (33) in Artemisia annua, and has shown that although the greatest incorporation normally occurs from (31), the presence of phosphate-cleaving enzymes reverses this situation.…”
Section: Pegolettia ~Enegalensis~~ and In The Oil Of Chamaemelum F U ...mentioning
confidence: 99%
“…34 Linalool oxide (86) rearranges, under acid catalysis, to give carvenone (87), together with the cyclopentenone(88) and the dienone(89) 135. Treatment with formic acid converts 10-hydroxygeranyl acetate (90) into the terpineol derivative (9 I), and methyl 10-hydroxygeranyl ether(92) gives(93) with BF3 -Et,O in dichloromethane. 36…”
mentioning
confidence: 99%
“…~, of experiments with cell cultures of Berberis species have shown that jatrorrhizine (55) is formed via (9-reticuline (40) and berberine (54), i.e. the transfer of a methyl group occurs from one oxygen [at C-6 in (40)] to another [at C-2 in (55)] by way of a methylenedioxy-group. This is an observation which has not previously been noted.…”
Section: Ohmentioning
confidence: 99%